Production of Pectin as a Relevant Tool for by-Products Management Resulting from Four Tropical Edible Fruits Processing: Extraction Yield, Physicochemical and Functional Properties of Pectin Powder - BAMBA, Bio Sigui Bruno; ’GOUIN, Joelle-Annabelle; KOUASSI, Esaie Kouadio Appiah; KOMENAN, Ayemene Cedrick Ardin; AKRE, Marie Stella Hermance; SORO, Doudjo; SORO, Yade Rene (International Journal of Chemical and Process Engineering Research, 2020)
The appropriate re-use ways of fruit processing by-products remains a central concern for scientist and industry, especially in the current context of circular economy. Thus, this study aimed to investigate the valorization of four most processing fruit peel (orange peel, lemon, grapefruit, and avocado) into pectin as well as compare to commercial ones. The pectin yield and their physicochemical properties including ash content, water content, pH, titratable acidity and functional properties, in term of solubility and viscosity, were determined. The increasing fraction of lemon pectin was incorporated to two garden soil (black and arable) and their water holding capacity were also evaluated. The hydrochloric acid extraction method was performed to extract pectin. The results revealed that lemon peel pectin yield (25.80 %) was higher than those of orange (19.1%) followed by grapefruit (16.36%) and avocado (2.93%). Furthermore, commercial and orange peel pectin showed the highest (43.01±1.06 g/100g w.b) and the lowest (13.33±0.31 g/100g w.b) moisture contents respectively. In addition, orange peel pectin had the highest pH (2.98) similar to that of commercial pectin (3.00). Moreover, grapefruit and orange peel pectin demonstrated the highest water solubility values (≈ 55 g/100g w.d) while lemon pectin was found to be the most viscous (1.50±0.02 mPa.s) and avocado the less viscous (0.11±0.01 mPa.s). In addition, when incorporated to garden soils, lemon pectin increase soils water retention capacity. This trend was found to be high for black soil.